Process evaluation of the MOSAIC trial: treatment experience of two psychological therapies for out-patient treatment of Anorexia Nervosa. Issue 1 (December 2016) - Zainal, Kelly; Renwick, Beth; Keyes, Alexandra; Lose, Anna; Kenyon, Martha; DeJong, Hannah; Broadbent, Hannah; Serpell, Lucy; Richards, Lorna; Johnson-Sabine, Eric; Boughton, Nicky; Whitehead, Linette; et al.
Abstract Background This study is part of a series of process evaluations within the MOSAIC Trial (Maudsley Outpatient Study of Treatments for Anorexia Nervosa and Related Conditions). This randomised controlled trial (RCT) compared two psychological treatments, the Maudsley Model for Treatment of Adults with Anorexia Nervosa (MANTRA) and Specialist Supportive Clinical Management (SSCM) for adult outpatients with Anorexia Nervosa. The present process study integrates quantitative (treatment acceptability and credibility) and qualitative (written) feedback to evaluate patients' treatment experiences. Method All 142 MOSAIC participants were asked to (a) rate treatment acceptability and credibility on visual analogue scales (VAS) at six and 12 months post-randomisation, and (b) provide written feedback regarding their views on their treatment at 12 months. Transcripts were first analysed thematically and then rated according to the global valence of feedback (positive, mixed/negative). Results 114/142 (80.3 %) MOSAIC participants provided VAS data and 82 (57.7 %) provided written feedback. At 12 months, MANTRA patients gave significantly higher acceptability and credibility ratings compared to SSCM patients. A significantly higher proportion of MANTRA patients provided written feedback. MANTRA patients also tended to write in more detail and to give globally more positive feedback when compared to individuals receiving SSCM. Qualitative themes suggest that patients experienced the two treatments differently in terms of characteristics and outcomes. Conclusions This study highlights the benefits of incorporating qualitative and quantitative data into RCT process evaluations. MANTRA patients were more willing to express their views on treatment and generally felt more positively about this than those receiving SSCM.